Viral co‐infection with human respiratory syncytial virus in suspected acute and severe respiratory tract infections during COVID‐19 pandemic in Yaoundé, Cameroon, 2020–2021. Issue 3 (29th March 2023) - Moumbeket Yifomnjou, Moïse Henri; Monamele, Gwladys Chavely; Njankouo‐Ripa, Mohamadou; Fatawou Modiyinji, Abdou; Ngoupo, Paul Alain; Boyomo, Onana; Njouom, Richard
Abstract: Background: Acute lower respiratory tract infections (ALRIs) are one one of the leading causes of morbidity and mortality among people of all ages worldwide, particularly in low‐ and middle‐income countries (LMICs). The purpose of this study was to determine epidemiological characteristics of respiratory viruses in acute respiratory infection (ARI) patients during the COVID‐19 pandemic in Yaoundé, Cameroon. Methods: Patients were monitored for respiratory symptoms as part of the surveillance of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and other respiratory viral infections. Patients of all ages with respiratory symptoms less than 5 days were considered. Sociodemographic and clinical data as well as nasopharyngeal samples was collected from patients. Nasopharyngeal samples were tested for SARS‐CoV‐2, influenza, and respiratory syncytial virus (RSV) using real‐time reverse‐transcription polymerase chain reaction methods. Virus distribution and demographic data were analyzed with R version 2.15.1. Results: From July 2020 to October 2021, 1120 patients were included. The overall viral detection rate was 32.5%, including 9.5% for RSV, 12.6% for influenza virus and 12.8% for SARS‐CoV‐2. Co‐infections were detected in 6.9% of positive cases. While RSV and influenza virus showed seasonal trends, SARS‐CoV‐2 was detected throughout the study period. Conclusion: We found that during COVID‐19 pandemic, respiratory viruses play an important role in etiology of influenza‐like illness in Cameroon, and this observation was true for patients of all ages.